Expert System in the Application of Learning Models with Forward Chaining Method - Herawan Hayadi, B; Bastian, Adolf; Rukun, Kasman; Jalinus, Nizwardi; Lizar, Yaslinda; Guci, Asriwan (International Journal of Engineering and Technology, 2018)
Expert System (ES) is one of the course subject contained in the Department of Information Engineering, University of Pasir Pengaraian (UPP). There are several methods in ES, and one of them is Forward Chaining Method. This method is quite difficult to understand such that 30.1% of students did not pass the course. Therefore we need a tool or model of learning in the delivery of this Forward Chaining Method.Â Â